Mobile Commerce Establishment for Livestock Marketing Development in West Sumatera: An Approach to Systems Requirement Analysis - Fitrimawati,; Hellyward, James; Aisuwarya, Ratna (International Journal of Psychosocial Rehabilitation, 2020)
A new innovation available via internet program can be accepted and adopted for it easily when integrated with a traditional method. Majority in West Sumatera, that the livestock market was still classified as the traditional method and had not undergone a modernization yet, while still being shown a function in the livestock marketing forms such as the distribution, the price formation, and the promotion; each of them was not still optimal in West Sumatera yet. Therefore, the development of the livestock market by mobile commerce establishment can overcome problems about the distribution, the price formation, and the promotion above. The purpose of this research has to be analyzed requirement of system for the mobile commerce establishment for the livestock marketing development in West Sumatera. Methodology is taken a System Development Life Cycle (SDLC); it is a method which shows about the life cycle of system development in a design and information construction. Primarily the data are issued from the secondary data. So that the data analysis technique usage was as the descriptive method and use for case the diagram usage. The diagram usage of the approachable analysis system needs the livestock marketing by the mobile commerce establishment to produce the functional analysis and nonfunctional usages in West Sumatera. The analysis system usages are displayed in the use case diagram forms.